Evolution of the Concept of Evolution - Mikhailovsky, George (Journal of Evolutionary Science, 2018)
A historical and conceptual review traces how evolutionary theory has expanded from classical selection to modern syntheses incorporating development, epigenetics, and systems thinking. Implications for research and science communication are discussed.
Keywords: Evolution; Evolutionary Theory; Selection; Epigenetics; Science Communication